ANALYSIS OF THE COMPLEXITY OF THE SECURITY SYSTEM AT HANG NADIM INTERNATIONAL AIRPORT IN BATAM IN MANAGING THREATS FROM DANGEROUS GOODS USING A THEORETICAL AND EMPIRICAL APPROACH - Auzan Firdaus, Dandy; Rochmawati, Laila; Purwayudhaningsari, Ranatika (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Airport security systems play an important role in preventing potential threats, particularly those involving dangerous goods that could compromise flight safety. Hang Nadim Batam International Airport is one of the national vital objects facing challenges in managing dangerous goods carried intentionally or unintentionally by passengers. This study aims to analyze the complexity of the security system in managing these threats using relevant theoretical and empirical approaches. The study examines national policies, particularly Minister of Transportation Decision No. KM 39 of 2024,]as a reference for managing dangerous goods in the airport environment. The empirical approach was conducted through direct observation, interviews with security personnel, and analysis of field findings related to hazardous materials at various checkpoints such as PSCP, HBSCP, and cargo areas. This study uses a theoretical and empirical approach as the analytical framework. The results of the study indicate that the security system at Hang Nadim Airport is complex and adaptive. This is reflected in the high number of hazardous materials found and the mitigation procedures implemented. The system is in line with the provisions of KM 39 of 2024, although there are still challenges in terms of technical aspects and human resources. These findings confirm the hypothesis that the security system implemented is comprehensive and responsive to the dynamics of threats.